A kind of new method of intelligent trust engineering metrics (ITEM) for application of mobile ad hoc network. Issue 5 (23rd January 2020) - Zhang, Degan; Gong, Changle; Jiang, Kaiwen; Zhang, Xiaodan; Zhang, Ting
Abstract : Purpose: This paper aims to put forward a kind of new method of intelligent trust engineering metrics for application of mobile ad hoc network (MANET). Design/methodology/approach: The new method calculates the communication trust by using the number of data packets among the nodes of MANET, predicts intelligently the trust and calculates the comprehensive trust based on the historical trust; then calculates the energy trust based on the residual energy of the nodes of MANET, calculates the direct trust based on the communication trust and energy trust. The new method calculates the recommendation trust based on the recommendation reliability; adopts the adaptive weighting to calculate the integrated direct trust by considering the direct trust with recommendation trust. Findings: Based on the integrated direct trust and the factor of trust propagation distance, the indirect trust among the nodes of MANET is calculated. The above process can be optimized based on the dynamic machine learning presented in this study. The advantage of the new method is its intelligent ability to discover malicious nodes. Originality/value: The advantage of the new method is its intelligent ability to discover malicious nodes which can partition the network by falsely reporting other nodes as misbehaving and proceeds to protect the network. The authors have done the experiments based on the tool kits such as NS3, QualNet, OMNET++ and MATLAB. The experimental results show that this study's approach can effectively avoid the attacks of malicious nodes, and more conformable to the actual engineering application of MANET.